Solid-state lithium battery and preparation method thereof and electrical equipment

By setting up a polymer modification layer in a solid-state lithium battery, the side reactions caused by the contact between the metal lithium negative electrode and the solid electrolyte and the growth of lithium dendrites are solved, and the safety and energy density of the battery are improved.

CN115084642BActive Publication Date: 2025-04-29SUNWODA ELECTRONICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210922271.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2025-04-29
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

In the prior art, all-solid-state batteries that use metal lithium negative electrodes. During the battery cycle, the metal lithium negative electrodes come into contact with the solid electrolyte and easily react side-reaction, forming a high-impedance interface layer, and lithium dendrites are easily formed on the surface of the metal lithium negative electrodes, and lithium dendrites are easily pierced through the separator, resulting in battery short circuits and serious safety problems.

Method used

A polymer modification layer is arranged between the lithium negative electrode sheet and the sulfide electrolyte layer. The polymer modification layer is composed of a polymer and a lithium salt. The lithium salt is dispersed in the polymer and is prepared and formed by in-situ polymerization.

Benefits of technology

The sulfide electrolyte layer is avoided to contact the lithium negative electrode sheet directly to avoid the occurrence of side reactions. At the same time, the polymer modified layer has excellent ionic conductivity and expansion and contraction ability, inhibiting the generation of lithium dendrites, reducing the risk of battery short circuits, and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115084642B_ABST
    Figure CN115084642B_ABST
Patent Text Reader

Abstract

The present application provides a solid-state lithium battery and its preparation method and electrical equipment. The solid-state lithium battery includes a lithium negative electrode sheet, a polymer modified layer, a sulfide electrolyte layer and a positive electrode sheet stacked in sequence, wherein the material of the polymer modified layer includes a polymer and a lithium salt, and the lithium salt is dispersed in the polymer. Applying the technical solution of the present application, the solid-state lithium battery provided by the present application is provided with a polymer modified layer between the lithium negative electrode sheet and the sulfide electrolyte layer, thereby avoiding direct contact between the sulfide electrolyte layer and the lithium negative electrode sheet and the occurrence of side reactions. At the same time, the polymer modified layer has excellent ion conductivity and expansion and contraction capabilities, ensuring the transmission of lithium ions in the polymer modified layer and slowing down the damage caused by the volume change of the lithium negative electrode sheet during the charge and discharge process. At the same time, the polymer modified layer can also effectively inhibit the generation of lithium dendrites, reduce the risk of battery short circuit, and improve safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a solid-state lithium battery and a preparation method and electrical equipment thereof. Background Art

[0002] Lithium metal anode has long been considered the best anode to improve the energy density of lithium batteries because it has the lowest electrochemical potential (-3.04 V vs. SHE) and low density (0.53 g cm -1 ) and a very high theoretical capacity (3860mAhg -1 ). However, lithium metal is very active and easily reacts with other substances, and it is easy to form lithium dendrites on the metal surface. During the battery cycle, lithium dendrites can easily pierce the separator, causing internal short circuits and serious safety problems.

[0003] The use of high-strength solid electrolytes to prepare all-solid-state batteries is expected to realize the application of metal lithium negative electrodes and improve the energy density of batteries. However, most solid electrolytes are unstable to lithium metal, and a high-impedance interface layer will be formed during the battery cycle. In addition, the solid electrolyte has poor contact with metal lithium and uneven current distribution, which promotes the growth of lithium dendrites. The dendrites pass through the gaps in the solid electrolyte to reach the positive electrode, causing the battery to short-circuit.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The main purpose of the present application is to provide a solid-state lithium battery and a preparation method and electrical equipment thereof, so as to solve the technical problems in the prior art that, during the battery cycle, the metal lithium negative electrode of the all-solid-state battery using the metal lithium negative electrode is prone to side reactions when in contact with the solid electrolyte, forming a high-impedance interface layer, and lithium dendrites are easily formed on the surface of the metal lithium negative electrode, and the lithium dendrites are easy to pierce the diaphragm, causing battery short circuit and serious safety problems.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a solid-state lithium battery is provided, which includes a lithium negative electrode sheet, a polymer modified layer, a sulfide electrolyte layer and a positive electrode sheet stacked in sequence, wherein the material of the polymer modified layer includes a polymer and a lithium salt, and the lithium salt is dispersed in the polymer.

[0007] Furthermore, in the polymer modified layer, the mass content of lithium salt is 4.95% to 15%.

[0008] Further, the polymer includes at least one of polyvinylene carbonate, polyethylene glycol methyl ether polymethacrylate, polyethylene glycol methyl ether polymethacrylate, polyethylene glycol polymethacrylate, polyethylene glycol polydimethacrylate or polyethylene glycol polydiacrylate.

[0009] Further, the lithium salt includes at least one of LiBF4, LiPF6, LiTFSI or LiBOB.

[0010] Furthermore, the polymer modified layer is prepared by in-situ polymerization of a raw material mixture including a polymer precursor, a lithium salt and an initiator.

[0011] Furthermore, in terms of mass percentage, in the raw material mixture, the polymer precursor accounts for 85% to 95%, the lithium salt accounts for 4.95% to 15%, and the initiator accounts for 0.01% to 0.1%.

[0012] Furthermore, the polymer precursor includes at least one of vinylene carbonate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol diacrylate; the number average molecular weight of polyethylene glycol methyl ether methacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol diacrylate is independently 200 to 1000; the initiator includes at least one of an azo compound or a peroxide compound, wherein the azo compound includes at least one of azobisisobutyronitrile or azobisisoheptylnitrile, and the peroxide compound includes at least one of dibenzoyl peroxide or dodecanoyl peroxide.

[0013] Furthermore, the thickness of the polymer modified layer is 2 to 15 μm, preferably 5 to 12 μm.

[0014] Furthermore, the sulfide electrolyte layer is mainly formed by pressing a granular first sulfide electrolyte, wherein the first sulfide electrolyte includes Li 4-x Ge 1-x P x S 2(1-x) , Li2S-Al2S3-P2S5, Li2SP2S5-LiI, Li2S-P2S5-LiBr, Li2S-P2S5-LiBH4, Li2S-P2S5-Ge 0.35 Ga 0.05 Se 0.60 , at least one of 67Li2S-33P2S5, 75Li2S-25P2S5, 70Li2S-30P2S5, LiPS4, Li6PS5Cl, 75LiS-15P2S5-10P2O5, x=0.55~1.

[0015] According to another aspect of the present application, a method for preparing a solid-state lithium battery is also provided, the method comprising: step S1, mixing a polymer precursor, a lithium salt and an initiator to obtain a raw material mixture; step S2, coating the raw material mixture on one surface of a sulfide electrolyte layer to form a polymer layer to be cured, placing a lithium negative electrode sheet in the polymer layer to be cured, placing a positive electrode sheet on another surface of the sulfide electrolyte layer, so that the positive electrode sheet, the sulfide electrolyte layer, the polymer layer to be cured and the lithium negative electrode sheet are stacked in sequence; step S3, in-situ polymerizing the polymer layer to be cured, curing the polymer layer to be cured to form a polymer modified layer, and obtaining a solid-state lithium battery. Further, the method for preparing the sulfide electrolyte layer comprises the following steps: mixing and pressing a granular first sulfide electrolyte in sequence to obtain a sulfide electrolyte layer.

[0016] Furthermore, the pressing pressure is 300-450 MPa, and the pressing time is 1-10 min.

[0017] Furthermore, the positive electrode sheet is formed by pressing the positive electrode active material and the second sulfide electrolyte.

[0018] Furthermore, the mass ratio of the positive electrode active material to the second sulfide electrolyte is (65-75):(35-25).

[0019] Furthermore, the positive electrode active material includes at least one of NCM811, NCM622, NCM523, lithium cobalt oxide or lithium iron phosphate.

[0020] According to the third aspect of the present application, an electrical device is also provided, which comprises any solid-state lithium battery provided in the first aspect or a solid-state lithium battery obtained by any preparation method provided in the second aspect.

[0021] By applying the technical solution of the present application, the solid-state lithium battery provided by the present application is provided with a polymer modified layer between the lithium negative electrode sheet and the sulfide electrolyte layer, which avoids direct contact between the sulfide electrolyte layer and the lithium negative electrode sheet and the occurrence of side reactions. At the same time, the polymer modified layer has excellent ion conductivity and expansion and contraction capabilities, which ensures the transmission of lithium ions in the polymer modified layer and slows down the damage caused by the volume change of the lithium negative electrode sheet during charging and discharging. At the same time, the polymer modified layer can also effectively inhibit the generation of lithium dendrites, reduce the risk of battery short circuit, and improve safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0023] Figure 1A schematic diagram showing the structure of a solid-state lithium battery assembly in a solid-state lithium battery provided in Example 1 of the present application is shown; and

[0024] The above drawings include the following reference numerals:

[0025] 110. lithium negative electrode sheet; 120. polymer modification layer; 130. sulfide electrolyte layer. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] As analyzed in the background technology of this application, in the prior art, all-solid-state batteries using metal lithium negative electrodes are prone to side reactions when the metal lithium negative electrode contacts the solid electrolyte during the battery cycle, forming a high-impedance interface layer, and lithium dendrites are prone to form on the surface of the metal lithium negative electrode, which are prone to pierce the diaphragm, resulting in battery short circuits and serious safety issues. In order to solve this problem, this application provides a solid-state lithium battery assembly and a solid-state lithium battery and electrical equipment containing the same.

[0028] In a typical embodiment of the present application, a solid-state lithium battery is provided, which includes a lithium negative electrode sheet, a polymer modification layer, a sulfide electrolyte layer and a positive electrode sheet stacked in sequence, wherein the polymer modification layer includes a polymer and a lithium salt, and the lithium salt is dispersed in the polymer.

[0029] By applying the technical solution of the present application, the solid-state lithium battery provided by the present application is provided with a polymer modified layer between the lithium negative electrode sheet and the sulfide electrolyte layer, which avoids direct contact between the sulfide electrolyte layer and the lithium negative electrode sheet and the occurrence of side reactions. At the same time, the polymer modified layer has excellent ion conductivity and expansion and contraction capabilities, which ensures the transmission of lithium ions in the polymer modified layer and slows down the damage caused by the volume change of the lithium negative electrode sheet during charging and discharging. At the same time, the polymer modified layer can also effectively inhibit the generation of lithium dendrites, reduce the risk of battery short circuit, and improve safety.

[0030] There is no limitation on the type of the above polymers, and any polymer with excellent expansion and contraction properties can be used. From the perspective of improving the electrical conductivity of the polymer, the polymer can be selected from any one of polyvinyl carbonate, polyethylene glycol methyl ether polymethacrylate, polyethylene glycol polymethacrylate, polyethylene glycol polydimethacrylate or polyethylene glycol polydiacrylate, or a composite formed by two or more polymers.

[0031] In order to further improve the ionic conductivity of the polymer modified layer, the number average molecular weight of polyvinylene carbonate, polyethylene glycol methyl ether polymethacrylate, polyethylene glycol polymethacrylate, polyethylene glycol polydimethacrylate or polyethylene glycol polydiacrylate is independently 200-1000.

[0032] The type of the above lithium salt is not limited, and any lithium salt with excellent ion conductivity can be used. In order to improve the ion conductivity and the dispersibility of the lithium salt in the polymer, the lithium salt can be selected from any one of LiBF4, LiPF6, LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) or LiBOB (lithium bis(oxalatoborate)), or a mixed lithium salt formed by two or more lithium salts.

[0033] In order to further improve the ion conductivity and expansion and contraction capabilities of the polymer modified layer, the mass content of the lithium salt in the polymer modified layer is 4.95% to 15%.

[0034] When the content of lithium salt is too low, it is not conducive to improving the ionic conductivity of the polymer modified layer. When the content of lithium salt is too high, the expansion and contraction ability of the polymer modified layer is poor. When the content of lithium salt in the polymer modified layer is 4.95% to 15%, the polymer modified layer has both better ionic conductivity and expansion and contraction performance.

[0035] Typically but not limitatively, in the polymer modified layer, the mass content of the lithium salt is 4.95%, 5%, 8%, 10%, 12%, 15% or a range consisting of any two values; the number average molecular weight of polyvinyl carbonate, polyethylene glycol methyl ether polymethacrylate, polyethylene glycol polymethacrylate, polyethylene glycol polydimethacrylate or polyethylene glycol polydiacrylate is 200, 300, 400, 475, 500, 550, 600, 750, 900, 1000 or a range consisting of any two values.

[0036] In order to reduce the use of solvents and improve the environmental friendliness during the preparation of the polymer modification layer, the raw materials of the polymer modification layer are prepared by in-situ polymerization of a raw material mixture of a polymer precursor, a lithium salt and an initiator. In terms of mass percentage, in the raw material mixture, the polymer precursor accounts for 85% to 95%, the lithium salt accounts for 4.95% to 15%, and the initiator accounts for 0.01% to 0.1%.

[0037] The type of the initiator is not limited, and any substance capable of initiating a polymer precursor may be used. From the perspective of improving initiation efficiency, the initiator is preferably any one of an azo compound or a peroxide compound. Azo compounds include but are not limited to any one of azobisisobutyronitrile or azobisisoheptanenitrile, and peroxide compounds include but are not limited to any one of dibenzoyl peroxide or dodecanoyl peroxide.

[0038] Typically but not limiting, in the raw material mixture, the mass proportion of the polymer precursor is 85%, 88%, 90%, 92%, 95% or a range consisting of any two values; the mass proportion of the lithium salt is 4.95%, 5%, 8%, 10%, 12%, 15% or a range consisting of any two values; the mass proportion of the initiator is 0.01%, 0.02%, 0.05%, 0.08%, 0.1% or a range consisting of any two values.

[0039] In some embodiments of the present application, the above-mentioned sulfide electrolyte layer is pressed from a granular first sulfide electrolyte, so that in the sulfide electrolyte layer, there are certain pores between the granular first sulfides, and the polymer in the polymer modification layer during the in-situ polymerization preparation process can penetrate into the gaps between the granular first sulfides, further inhibiting the growth of lithium dendrites. Specifically, since the polymer precursor penetrates deeply into the interior of the sulfide electrolyte, the gaps between the sulfide electrolyte particles can be reduced after in-situ polymerization. The lithium dendrites will be blocked by the polymer when growing along the gaps, preventing the lithium dendrites from growing along the gaps between the particles, thereby achieving the effect of further preventing the growth of lithium dendrites.

[0040] In order to further improve the preparation efficiency of the sulfide electrolyte layer, the preparation method of the sulfide electrolyte layer includes the following steps: mixing and pressing the granular first sulfide electrolyte in sequence to obtain the sulfide electrolyte layer.

[0041] The pressing pressure is not limited. To improve the pressing efficiency, the pressing pressure is 300-450 MPa and the pressing time is 1-10 min.

[0042] The type of the first sulfide electrolyte is not limited, including but not limited to Li 4-x Ge 1-x P x S 2(1-x) (x=0.55~1), Li2S-Al2S3-P2S5, Li2SP2S5-LiI, Li2S-P2S5-LiBr, Li2S-P2S5-LiBH4, Li2S-P2S5-Ge 0.35 Ga 0.05 Se 0.60 , any one of 67Li2S-33P2S5, 75Li2S-25P2S5, 70Li2S-30P2S5, LiPS4, Li6PS5Cl, 75LiS-15P2S5-10P2O5, or a mixture of two or more sulfide electrolytes.

[0043] Typically but not limitatively, in the process of preparing the sulfide electrolyte layer, the pressing pressure is 300 MPa, 320 MPa, 350 MPa, 380 MPa, 400 MPa, 420 MPa, 450 MPa or a range consisting of any two values; the pressing time is 1 min, 2 min, 5 min, 8 min, 10 min or a range consisting of any two values.

[0044] In a second typical embodiment of the present application, a preparation method for the above-mentioned solid-state lithium battery is also provided, and the preparation method comprises the following steps: step S1, mixing a polymer precursor, a lithium salt and an initiator to obtain a raw material mixture; step S2, coating the raw material mixture on one surface of the sulfide electrolyte layer to form a polymer layer to be cured, and then arranging the lithium negative electrode sheet on the polymer layer to be cured, and arranging the positive electrode sheet on the other side of the sulfide electrolyte layer, so that the positive electrode sheet, the sulfide electrolyte layer, the polymer layer to be cured and the lithium negative electrode sheet are stacked in sequence; step S3, in-situ polymerizing the polymer layer to be cured, and curing the polymer layer to be cured to form a polymer modification layer to obtain the solid-state lithium battery assembly.

[0045] In the above step S3, the in-situ polymerization is used to prepare the polymer modified layer, which can not only improve the preparation efficiency of the polymer modified layer, but also facilitate the penetration of the polymer modified layer into the sulfide electrolyte layer, thereby further inhibiting the growth of lithium dendrites.

[0046] In order to further reduce energy waste,

[0047] The temperature of the in-situ polymerization is 40-150° C., and the time is 1-12 hours. Especially when the temperature of the in-situ polymerization is 75-90° C., and the time is 4-8 hours, it is more conducive to improving the efficiency of the in-situ polymerization.

[0048] Typically but not limitatively, the temperature of the in-situ polymerization is 40°C, 50°C, 60°C, 70°C, 75°C, 80°C, 85°C, 90°C, 100°C, 120°C, 150°C or a range consisting of any two values; the time of the in-situ polymerization is 1h, 2h, 4h, 5h, 6h, 7h, 8h, 10h, 12h or a range consisting of any two values.

[0049] In order to further improve the ionic conductivity of the above-mentioned solid-state lithium battery and inhibit the growth of lithium dendrites, the thickness of the above-mentioned polymer modification layer is 1 to 15 μm, especially when the thickness of the polymer modification layer is 5 to 12 μm, which is more conducive to taking into account both excellent ionic conductivity and battery safety performance.

[0050] The type of the positive electrode sheet is not limited, and any positive electrode sheet that can be used in a solid-state lithium battery can be used. From the perspective of improving the ion transmission efficiency of the solid-state lithium battery, the positive electrode sheet is formed by mixing the positive electrode active material and the second sulfide electrolyte and then pressing them.

[0051] In order to further improve the ion transfer efficiency, the mass ratio of the positive electrode active material and the second sulfide electrolyte is (65-75):(35-25).

[0052] The above positive electrode active material is not limited, and can be any positive electrode active material that can be used for the positive electrode of a solid-state lithium battery, including but not limited to any one of NCM811, NCM622, NCM523, lithium cobalt oxide or lithium iron phosphate, or a mixture of two or more positive electrode active materials.

[0053] The type of the second sulfide electrolyte is the same as that of the first sulfide electrolyte, which will not be described in detail here.

[0054] In a third typical embodiment of the present application, an electrical device is also provided, which includes any solid-state lithium battery assembly provided in the first typical embodiment or any solid-state lithium battery provided in the third typical embodiment.

[0055] The above-mentioned electrical equipment may be, but is not limited to, electric cars, battery cars, ships, spacecraft, mobile phones, tablets, laptops, electric toys, electric tools, etc. Among them, spacecraft may include airplanes, rockets, space shuttles and spacecrafts, etc.; electric toys may include fixed or mobile electric toys, such as electric tank toys, game consoles, electric car toys, electric ship toys and electric airplane toys, etc.

[0056] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0057] Example 1

[0058] This embodiment provides a solid-state lithium battery, which includes a solid-state lithium battery component. The cross-sectional structure diagram of the solid-state lithium battery component is as shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the solid-state lithium battery assembly includes a lithium negative electrode sheet 110, a polymer modified layer 120 and a sulfide electrolyte layer 130 which are stacked in sequence. The solid-state lithium battery also includes a positive electrode sheet, which is stacked with the solid-state lithium battery assembly, and the positive electrode sheet, the sulfide electrolyte layer 130, the polymer modified layer 120 and the lithium negative electrode sheet 110 are stacked in sequence.

[0059] The solid-state lithium battery is prepared according to the following steps:

[0060] (1) A polymer precursor, a lithium salt and an initiator are mixed uniformly in a mass ratio of 90:9.9:0.1 to obtain a raw material mixture; wherein the polymer precursor is polyethylene glycol methyl ether methacrylate with a number average molecular weight of 475, the lithium salt is LiBF4, and the initiator is azobisisobutyronitrile.

[0061] (2) 100 mg of a first sulfide electrolyte with a particle size of 10 μm was pressed at a pressure of 380 MPa for 1 min to form a sheet-like sulfide electrolyte layer 130 with a thickness of 100 μm, wherein the first sulfide electrolyte was LPSCl, which refers to Li6PS5Cl.

[0062] (3) The positive electrode active material and the second sulfide electrolyte are mixed in a mass ratio of 70:30 to obtain a mixture of 10 mg of the positive electrode active material and the second sulfide electrolyte, wherein the positive electrode active material is NCM622; the second sulfide electrolyte is LPSCl; the mixture of the positive electrode active material and the second sulfide electrolyte is uniformly arranged on one side of the sulfide electrolyte layer 130, and pressed at a pressure of 400 MPa for 10 minutes to obtain a positive electrode sheet attached to the sulfide electrolyte layer 130, wherein the thickness of the positive electrode sheet is 200 μm.

[0063] (4) evenly disposing a raw material mixture formed by a polymer precursor, a lithium salt and an initiator on the other side of the sulfide electrolyte layer 130 to form a polymer layer to be cured attached to the other side of the electrolyte layer 130;

[0064] (5) Placing a lithium negative electrode sheet 110 on the polymer layer to be cured, raising the temperature to 80°C and keeping the temperature for 5 hours, allowing the polymer layer to be cured to form a polymer modified layer 120, thereby obtaining a solid-state lithium battery in which the lithium negative electrode sheet 110, the polymer modified layer 120, the lithium negative electrode sheet 110 and the positive electrode sheet are stacked in sequence; wherein the thickness of the lithium negative electrode sheet is 20 μm, and the thickness of the polymer modified layer is 10 μm.

[0065] Example 2

[0066] The difference between this embodiment and embodiment 1 is that in step (1), the polymer precursor used is polyethylene glycol diacrylate with a number average molecular weight of 200.

[0067] Example 3

[0068] The difference between this embodiment and embodiment 1 is that in step (1), the polymer precursor used is polyethylene glycol diacrylate with a number average molecular weight of 1000.

[0069] Example 4

[0070] The difference between this embodiment and embodiment 1 is that in step (1), the polymer precursor used is polyethylene glycol diacrylate with a number average molecular weight of 800.

[0071] Example 5

[0072] The difference between this embodiment and embodiment 1 is that in step (1), the polymer precursor used is polyethylene glycol methacrylate with a number average molecular weight of 900.

[0073] Example 6

[0074] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of polymer precursor, lithium salt and initiator is 95:4.95:0.05.

[0075] Example 7

[0076] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of polymer precursor, lithium salt and initiator is 85:14.96:0.04.

[0077] Example 8

[0078] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of polymer precursor, lithium salt and initiator is 65:34.96:0.04.

[0079] Example 9

[0080] The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of polymer precursor, lithium salt and initiator is 98:1.96:0.04.

[0081] Example 10

[0082] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the thickness of the polymer modification layer is 5 μm.

[0083] Embodiment 11

[0084] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the thickness of the polymer modification layer is 12 μm.

[0085] Example 12

[0086] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the thickness of the polymer modification layer is 2 μm.

[0087] Example 13

[0088] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the thickness of the polymer modification layer is 15 μm.

[0089] Embodiment 14

[0090] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the thickness of the polymer modification layer is 1 μm.

[0091] Embodiment 15

[0092] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the thickness of the polymer modification layer is 20 μm.

[0093] Example 16

[0094] The difference between this embodiment and embodiment 1 is that in the solid-state lithium battery, the polymer modification layer is made of epoxy resin.

[0095] Embodiment 17

[0096] The difference between this embodiment and embodiment 1 is that in step (1), the polymer precursor is methacrylate.

[0097] Comparative Example 1

[0098] This comparative example provides a solid-state lithium battery, which is different from Example 1 in that no polymer modification layer is provided.

[0099] Test Example 1

[0100] The above solid-state lithium battery was tested for interface layer ion conductivity, symmetric battery polarization voltage, symmetric battery cycle time, full battery internal resistance and full battery life. The results are shown in Table 1 below.

[0101] Among them, the symmetrical battery structure is: Li-modified layer-LPSCl-modified layer-Li, and the full battery structure is: NCM622+LPSCl-LPSCl-modified layer-Li.

[0102] (1) The test method for the ionic conductivity of the interface layer is as follows: at room temperature, the electrochemical impedance spectroscopy was performed using a Biologie V-800 electrochemical workstation with a Fe-modified layer-Fe battery structure. The test range was 10 7 ~1Hz, the ionic conductivity of the interface layer is obtained;

[0103] (2) The test method for the polarization voltage and cycle time of the symmetrical battery is as follows: at room temperature, a symmetrical battery structure of Li-modified layer-LPSCl-modified layer-Li is used, and a blue electric charge and discharge test cabinet is used, with a charge and discharge current of 0.1 mA / cm 2 , the charge and discharge capacity is 0,1mAh / cm 2 , until the battery short circuit stops the test, the battery running time is the symmetrical battery cycle time;

[0104] (3) The test method for the internal resistance of the whole battery is as follows: at room temperature, the electrochemical impedance test of the whole battery is performed using a Biolog V-800 electrochemical workstation with a test range of 10 7 ~1Hz, and the internal resistance of the whole battery is obtained;

[0105] (4) The full battery life test method is: at room temperature, use a Blue Electric charge and discharge test cabinet to perform a charge and discharge cycle test on the full battery, with a charge and discharge rate of 0.1C, until the discharge capacity of the full battery decays to 80% of the initial discharge capacity, and record the number of cycles at this time.

[0106] Table 1

[0107]

[0108]

[0109] From the above description, it can be seen that the above-mentioned embodiments of the present application achieve the following technical effects: the solid-state lithium battery provided by the present application is provided with a polymer modified layer between the lithium negative electrode sheet and the sulfide electrolyte layer, which avoids direct contact between the sulfide electrolyte layer and the lithium negative electrode sheet and the occurrence of side reactions. At the same time, the polymer modified layer has excellent ion conductivity and expansion and contraction capabilities, which ensures the transmission of lithium ions in the polymer modified layer and slows down the damage caused by the volume change of the lithium negative electrode sheet during the charging and discharging process. At the same time, the polymer modified layer can also effectively inhibit the generation of lithium dendrites, reduce the risk of battery short circuit, and improve safety.

[0110] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises a lithium negative electrode sheet, a polymer modification layer, a sulfide electrolyte layer and a positive electrode sheet which are stacked in sequence; Wherein, the material of the polymer modification layer includes a polymer and a lithium salt, and the lithium salt is dispersed in the polymer; In the polymer modified layer, the mass content of the lithium salt is 4.95% to 15%; The polymer is selected from at least one of polyethylene glycol methyl ether polymethacrylate, polyethylene glycol polymethacrylate, polyethylene glycol polydimethacrylate or polyethylene glycol polydiacrylate; The lithium salt includes at least one of LiBF4, LiPF6, LiTFSI or LiBOB; The thickness of the polymer modified layer is 2-15 μm.

2. The solid-state lithium battery according to claim 1, characterized in that: The polymer modified layer is prepared by in-situ polymerization of a raw material mixture including a polymer precursor, a lithium salt and an initiator.

3. The solid-state lithium battery according to claim 2, characterized in that: In terms of mass percentage, in the raw material mixture, the polymer precursor accounts for 85% to 95%, the lithium salt accounts for 4.95% to 15%, and the initiator accounts for 0.01% to 0.1%.

4. The solid-state lithium battery according to claim 3, characterized in that: The polymer precursor is selected from at least one of polyethylene glycol methyl ether methacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol diacrylate; The number average molecular weight of the polyethylene glycol methyl ether methacrylate, the polyethylene glycol methacrylate, the polyethylene glycol dimethacrylate, the polyethylene glycol dimethacrylate, and the polyethylene glycol diacrylate are each independently 200 to 1000; The initiator includes at least one of an azo compound or a peroxide compound, wherein the azo compound includes at least one of azobisisobutyronitrile or azobisisoheptanenitrile, and the peroxide compound includes at least one of dibenzoyl peroxide or dodecanoyl peroxide.

5. The solid-state lithium battery according to any one of claims 1 to 4, characterized in that: The sulfide electrolyte layer is formed by pressing a raw material including a granular first sulfide electrolyte, wherein the first sulfide electrolyte includes Li 4-x Ge 1-x P x S 2(1-x) , Li2S-Al2S3-P2S5, Li2SP2S5-LiI, Li2S-P2S5-LiBr, Li2S-P2S5-LiBH4, Li2S-P2S5-Ge 0.35 Ga 0.05 Se 0.60 , at least one of 67Li2S-33P2S5, 75Li2S-25P2S5, 70Li2S-30P2S5, LiPS4, Li6PS5Cl, 75LiS-15P2S5-10P2O5, x=0.55~1.

6. The solid-state lithium battery according to any one of claims 1 to 4, characterized in that: The thickness of the polymer modified layer is 5-12 μm.

7. The method for preparing a solid-state lithium battery according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Step S1, mixing a polymer precursor, a lithium salt and an initiator to obtain a raw material mixture; Step S2, coating the raw material mixture on one surface of the sulfide electrolyte layer to form a to-be-cured polymer layer, placing a lithium negative electrode sheet on the to-be-cured polymer layer, and placing a positive electrode sheet on the other surface of the sulfide electrolyte layer, so that the positive electrode sheet, the sulfide electrolyte layer, the to-be-cured polymer layer and the lithium negative electrode sheet are stacked in sequence; Step S3, in-situ polymerizing the polymer layer to be cured, and curing the polymer layer to be cured to form a polymer modified layer to obtain the solid-state lithium battery.

8. The preparation method according to claim 7, characterized in that: The method for preparing the sulfide electrolyte layer comprises the following steps: sequentially mixing and pressing a granular first sulfide electrolyte to obtain the sulfide electrolyte layer; The pressing pressure is 300-450 MPa and the pressing time is 1-10 min.

9. The preparation method according to claim 7, characterized in that: The positive electrode sheet is formed by pressing the positive electrode active material and the second sulfide electrolyte; The mass ratio of the positive electrode active material to the second sulfide electrolyte is (65-75): (35-25); The positive electrode active material includes at least one of NCM811, NCM622, NCM523, lithium cobalt oxide or lithium iron phosphate.

10. An electrical device, characterized in that: A solid-state lithium battery comprising the solid-state lithium battery according to any one of claims 1 to 6 or a solid-state lithium battery obtained by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Solid-state lithium battery and electrode-diaphragm layer interface improvement method and application thereof

    CN112242560A